CD137 ligand signalling induces differentiation of primary acute myeloid leukaemia cells. (15th January 2014) - Cheng, Kin; Wong, Siew Cheng; Linn, Yeh Ching; Ho, Liam Pock; Chng, Wee Joo; Schwarz, Herbert
Summary CD137 ligand (CD137L), a member of the tumour necrosis factor family, is expressed as a cell surface molecule. Engagement of CD137L on haematopoietic progenitor cells induces monocytic differentiation, and in peripheral monocytes CD137L signalling promotes differentiation to mature dendritic cells. We hypothesized that CD137L signalling would also induce differentiation in transformed myeloid cells. Here we show that recombinant CD137 protein, which crosslinks CD137L and initiates reverse CD137L signalling in myeloid cells, induces morphological changes (adherence, spreading), loss of progenitor markers (CD117), expression of maturation markers (CD11b, CD13) and secretion of cytokines that are indicative of myeloid differentiation. Under the influence of CD137L signalling, acute myeloid leukaemia (AML) cells acquired expression of co‐stimulatory molecules (CD80, CD86, CD40), the dendritic cell marker CD83 and dendritic cell activities, enabling them to stimulate T cells. CD137L signalling induced differentiation in 71% (15 of 21) of AML samples, irrespective of French‐American‐British classification and CD137L expression level. However, the type of response varied with the AML subtype and patient sample. In summary, this study demonstrated that CD137L signalling induced differentiation in malignant cells of AML patients, and suggests that it may be worthwhile to investigate treatment with recombinant CD137 protein as a potential novel therapeutic approach for AML.